Drivers of teachers’ innovative behaviour in Tanzania’s secondary schools: is trust really a missing link? - Singogo, Patrick Christopher (Papers in Education and Development, 2024)
The study aimed to explore drivers of teachers’ innovative behaviour with the mediating role of trust. Seven hypotheses were developed based on social exchange theory and empirical studies. A structured questionnaire was used to collect data from 916 teachers in Tanzania. Using Partial Least Squares Structural Equation Modelling (PLS-SEM), the findings revealed that opportunism, cooperation, and trust significantly influence teachers’ innovative behaviour, while opportunism and cooperation also significantly influence trust. The findings also showed that trust mediates the associations between opportunism and teachers’ innovative behaviour and cooperation and teachers’ innovative behaviour. The study offers theoretical insights based on social exchange theory, highlighting that actions within employer-teacher relationships can directly influence attitude and behaviour, while attitudes can mediate the influence of these actions on behaviour. The findings suggest the need for managers to ensure the availability of cooperation while minimising opportunism to enhance both trust and innovative behaviour among employees.